Correlation between thyroid hormone level and efficacy of glucocorticoid in patients with minimal change disease - 谭嘉臻; 薛志强; 廖纯兴; 曾石养 (Linchuang shenzangbing zazhi)
Objective To study the correlation between thyroid hormone level and efficacy of glucocorticoid in patients with minimal change disease（MCD）.Methods A total of 55 patients with minimal change disease who hospitalized in Department of nephrology,Qingyuan People’s Hospital from January 2016 to May 2019 were selected as the study object.All the patient received glucocorticoid therapy and follow-up.Univariable analysis and multivariate analysis were used to analyze the influencing factors for remission with 4 weeks and 8 weeks of glucocorticoid therapy.The included variates included,age,gender,hemoglobin,serum creatinine,serum albumin,24-hour urine protein,glutamic-pyruvic transaminase,glutamic-oxaloacetic transaminase,triglycerides,total cholesterol,free triiodothyronine（fT3）,free thyroxine（fT4）,and serum thyrotrophin.Correlation between FT3,FT4,TSH and the time from intervention to remission was analyzed.By the ROC curve,the sensitivity,specificity and optical critical value of the variates with big influence coefficients in predicting remission within 4 weeks and within 8 weeks.Results In 55 patients with MCD,both FT3 and FT4 were significantly negatively correlated with the time from intervention to remission（P<0.01）,but there was no significant correlation between serum thyrotrophin and the time from intervention to remission（P>0.05）.Univariate analysis showed that serum creatinine,24-hour urine protein quantification,FT3,and FT4 were independent factors influencing remission within 4 weeks after glucocorticoid treatment;age,sex,serum creatinine,24-hour urine protein quantification,FT3,and FT4 were independent factors influencing patients’ remission within 8 weeks.The result of the binary Logistic regression model showed that FT3 was an independent factor that had greater impact on patients’ remission within 4 weeks and 8 weeks.The ROC curve showed that the optimal critical values for FT3 to predict the remission within 4 weeks and 8 weeks were 2.38 pmol/L and 2.23 pmol/L respectively,with the sensitivity 73.7% and 73.9% respectively,and the specificity of 70.6% and 88.9% respectively.Conclusions Thyroid hormone such as FT3,FT4,especially FT3,in patients with minimal change disease are correlative with the efficacy of glucocorticoid.Low FT3 level（with or without low FT4 level）may suggest decreased sensitivity to glucocorticoid,and FT3 can be used as one of the indicators to predict the remission of patients receiving glucocorticoid therapy within 4 weeks and 8 weeks.